CHARACTERISTICS OF GAP-GRADED ROADBASE MATERIAL BOUND WITH ROAD OYL - (NIM 269 92 019), Subarkah
Abstract : ROAD OYL is a resin modified emulsion formulated from natural forest ingredients and produced by Soil Stabilization Products Co., Inc., California, USA. The objective of the research programme described in this thesis was to compare the characteristics of roadbase aggregate stabilized with Road OYL with those of aggregate stabilized with bituminous binder. Gap-graded aggregate at the lower and upper limits of the grading envelope specified in BS 594 (1985) for roadbase material was used; 60 and 80 pen grade bitumens were selected for purposes of comparison with Road OYL. The preparation and testing of samples made with Road OYL followed the procedure proposed in a recent ASTM D4 Committee Working Document (1993); for the pen grade bitumens the conventional Marshall procedure was applied. The stability of specimens made with Road OYL was significantly lower than that of specimens made with 60 and 80 pen bitumens at both the lower and upper limits of the aggregate grading. Stabilities of 570 kg and 555 kg were determined for Road OYL specimens graded to the upper and lower limits, respectively; the corresponding values for specimens made with 60 pen and 80 pen bitumens were 1620 kg and 1060 kg and 1580 kg and 970 kg, respectively. Specimens made with Road OYL disintegrated rapidly when immersed in the water, a process probably facilitated by the relatively high air voids content of these mixes. In the case of conventional binder, specimens made with 60 pen bitumen were more susceptible to water damage than those made with 80 pen bitumen at both the upper and lower grading limits; for both bitumen types specimens made at the lower limit of the aggregate grading were less susceptible to water damage. Indirect tensile strength was influenced by temperature. Specimens made with Road OYL were less temperature-susceptible than those made with bitumens. The tensile strength of specimens made with Road OYL, at both the lower and upper limits of the aggregate grading, was greater at high temperature than that of specimens made with bitumen, but lower at low temperature. Tensile strength was also influenced by aggregate grading; specimens made at the upper grading had greater tensile strength than those made at the lower limit.